Dependence of drug efficacy on the metabolic activity of biofilm bacteria - Lian, Min (Nanyang Technological University, 2020)
Eradication of biofilms has been clinically challenging over the years as bacteria developed tolerance against antibiotics. To overcome this issue, an alternative treatment method is needed. A promising approach to the control of biofilms is weak acid therapy, which had shown great efficacy in complete eradication of biofilms at pH < pKa. Unlike monotropic weak acids, triprotic weak acids such as citric acid has selective bactericidal efficacy at pKa1<pH<pKa2 where it only eradicates cells at the core of the biofilm. It has been postulated that it is active against those cells in the core of the biofilm because they are inactive. To test this explanation for the selective activity of citric acid, we compared the efficacy of citric acid at pKa1<pH<pKa2 on static biofilms that were grown for 24 – 72 hours. Based on CFU counts and FDA/PI staining, we observed that citric acid does kill inactive cells at pKa1<pH<pKa2. We also found that the crystal violet assay was not a good indicator of drug efficacy as it does not differentiate between bacterial viability and total biomass. Thus, promising further work is needed to better understand the activity of citric acid against biofilms for future development as a biofilm control treatment.